Systematic studies in the genus Bulbinella Kunth (Asphodelaceae) - Perry, P. L. (Department of Biological Sciences, 2026)
Bulbinella Kunth is a comparatively small genus of the family Liliaceae sensu lato, wth distributions in the Cape Province of South Africa and in the main islands comprising New Zealand. A revision is given of Baker's 1896 systematic treatment of the genus in Flora capensis. The data sources for the revision include a detailed morphological study based on living material, seedling development, pollen structure, leaf anatomy, geographical distributions and ecology. is reviewed. Previous work on breeding biology. A comparison of the systematics of Bulbinella in South Africa and New Zealand is followed by some discussion on this unique disjunct distribution. For the taxonomic treatment existing type material was viewed as well as herbarium material from the main collections in South Africa and Europe. Of the 21 names originally attached to the genus, as enumerated in Index Kewensis, seven had previously been transferred to other genera, six have been placed in synonomy, one has been rejected and seven upheld. Nine new species and two new varieties are described. One previously described variety is raised to specific rank.